Synthesis of Batrachochytrium dendrobatidis infection in South America: amphibian species under risk and areas to focus research and disease mitigation. Issue 7 (8th April 2022) - Azat, Claudio; Alvarado‐Rybak, Mario; Solano‐Iguaran, Jaiber J.; Velasco, Aníbal; Valenzuela‐Sánchez, Andrés; Flechas, Sandra V.; Peñafiel‐Ricaurte, Alexandra; Cunningham, Andrew A.; Bacigalupe, Leonardo D.
Abstract : Amphibian chytridiomycosis, caused by Batrachochytrium dendrobatidis ( Bd ), has been recognized as the infectious disease causing the most catastrophic loss of biodiversity known to science, with South America being the most impacted region. We tested whether Bd prevalence is distributed among host taxonomy, ecoregion, conservation status and habitat preference in South America. Here we provide a synthesis on the extent of Bd infection across South America based on 21 648 molecular diagnostic assays, roles of certain species in the epidemiology of Bd and explore its association with the reported amphibian catastrophic declines in the region. We show that Bd is widespread, with a continental prevalence of 23.2%. Its occurrence in the region shows a phylogenetic signal and the probability of infection is determined by ecoregion, preferred habitat and extinction risk hosts' traits. The taxa exhibiting highest Bd occurrence were mostly aquatic amphibians, including Ranidae, Telmatobiidae, Hylodidae, Calyptocephalellidae and Pipidae. Surprisingly, families exhibiting unusually low Bd prevalence included species in which lethal chytridiomycosis and population declines have been described (genera Atelopus, Rhinoderma and Eleutherodactylus ). Higher than expected prevalence of Bd occurred mainly in amphibians living in association with mountain environments in the Andes and Atlantic forests, reflecting highly favourable Bd habitats in these areas. Invasive amphibian species (e.g. Lithobates catesbeianus and Xenopus laevis ) exhibited high Bd prevalence; thus we suggest using these as sentinels to understand their potential role as reservoirs, vectors or spreaders of Bd that can be subjected to management. Our results guide on the prioritization of conservation actions to prevent further biodiversity loss due to chytridiomycosis in the world's most amphibian diverse region.